TnP Peptide Suppresses Experimental Autoimmune Encephalomyelitis (EAE) in a Preclinical Mouse Model - Lima, Carla; Maleski, Adolfo Luis Almeida; Bernardo, Jefferson Thiago Gonçalves; Zelli, Vitor Cataldi; Komegae, Evilin Naname; Lopes-Ferreira, Monica (Frontiers in Immunology, 2022)
TnP is a family of patented synthetic peptides which is in a preclinical development stage with valuable potential therapeutic indication for multiple sclerosis (MS), an autoimmune demyelinating disease of the central nervous system (CNS). The use of a preclinical animal model, such as experimental autoimmune encephalomyelitis (EAE) has deepened our knowledge of the immunomodulatory functions of TnP as a drug. We have shown that TnP possesses a disease suppressive function in EAE, ameliorating disease severity by 40% and suppressing the accumulation of T helper (Th)1- and Th17-producing lymphocytes (by 55% and 60%, respectively) in CNS along with activated microglia/macrophages populations (by 33% and 50%, respectively), and also conferred a protective effect anticipating the remyelination process to day 66 compared to day 83 of untreated cuprizone-mice. Here we expanded our knowledge about its effects compared with current first-line disease-modifying therapies (DMT). We demonstrated that prophylactic treatment with TnP generated similar protection to betaseron (30%) or was more effective than glatiramer (44% versus 6%) or fingolimod (50% versus 19%) against the development of clinical symptoms. Although TnP controlled the leukocyte infiltration (87% versus 82%) into demyelinated areas of the spinal cord in the same way as betaseron and fingolimod, it was more effective (72% to 78% decrease) in the long-term control of neuronal degeneration compared to them. Also, when compared to glatiramer, TnP was more efficient in reversing leukocytes infiltration into the spinal cord (55% versus 24%), as well as induced a higher percentage of regulatory cells in spleen (2.9-fold versus 2.3-fold increase over vehicle-treated EAE mice) an in the spinal cord (8-fold versus 6-fold increase over vehicle-treated EAE mice). This specialized TnP profile for inducing immune tolerance and neuronal regeneration has significant therapeutic potential for the treatment of MS and other autoimmune diseases.